1987
DOI: 10.2135/cropsci1987.0011183x002700030008x
|View full text |Cite
|
Sign up to set email alerts
|

Response to Plant Densities and Nitrogen Levels for Four Maize Cultivars from Different Eras of Breeding1

Abstract: We evaluated the performance of maize (Zea mays L.) cultivars representing 10‐yr eras in 12 treatment combinations of plant densities and N levels. There were four open‐pollinated (OP) varieties and six 10‐yr (1930 to 1980) eras, four cultivars per era, of singlecross hybrids. A primary purpose was to compare the hybrids and eras for interaction with plant densities and N levels. The cultivars were grown for 2 yr near Ames, IA at densities of 34 445, 51 661, and 68 889 plants ha−1 and N levels of 0, 80, 160, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
51
0
8

Year Published

1992
1992
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 0 publications
10
51
0
8
Order By: Relevance
“…Nitrogen improves biomass production because it promotes a higher photosynthetic rate by an increase in crop radiation interception and in conversion efficiency into biomass (Novoa and Loamis, 1981). Results are consistent with those observed by Carlone and Russell (1987), O'Leary and Rehm (1990), Muchow and Sinclair (1994) and Cox et al (1993). These results confirms those repots from Ming and Mumpton (1989), McGilloway et al (2003), Gruener et al (2003) and Rehakova et al (2004) and also indicate that zeolite minerals are able to contribute to increasing N uptake through the control of retention of ammonium ion−formed by urea hydrolysis in the soil, due to zeolite high cation exchange capacity and ammonium withdrawal from soil solution (Bartz and Jones, 1983;Ferguson and Pepper, 1987).…”
Section: Resultssupporting
confidence: 92%
“…Nitrogen improves biomass production because it promotes a higher photosynthetic rate by an increase in crop radiation interception and in conversion efficiency into biomass (Novoa and Loamis, 1981). Results are consistent with those observed by Carlone and Russell (1987), O'Leary and Rehm (1990), Muchow and Sinclair (1994) and Cox et al (1993). These results confirms those repots from Ming and Mumpton (1989), McGilloway et al (2003), Gruener et al (2003) and Rehakova et al (2004) and also indicate that zeolite minerals are able to contribute to increasing N uptake through the control of retention of ammonium ion−formed by urea hydrolysis in the soil, due to zeolite high cation exchange capacity and ammonium withdrawal from soil solution (Bartz and Jones, 1983;Ferguson and Pepper, 1987).…”
Section: Resultssupporting
confidence: 92%
“…In absolute values, modern hybrid Ag 9012 presented an yield edge over the older materials that ranged from 1,350 to 1,500 kg ha -1 , depending on the amount of N applied to the soil. The impact of N on grain yield depicted in Figure 1 showed that hybrids cultivated in Southern Brazil during the last 40 years presented the same kind of behavior described by Castleberry et al (1984), Carlone & Russel (1987), Russel (1991) and Duvick (1994) for hybrids cultivated in the West US Corn Belt. Modern-day hybrid Ag 9012 had greater grain yield than did hybrids of earlier eras at all N rates evaluated in the trial.…”
Section: Resultssupporting
confidence: 56%
“…This yield enhancement can be largely attributed to the release of genetic superior hybrids, higher plant densities, increased use of chemical fertilizers, reduction of row spacing, improved cultural practices, better weed and pest control (Carlone & Russel, 1987;Dwyer et al, 1991;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A adubação do milho com N é importante, porque ele é um dos principais nutrientes que favorecem a elevação dos rendimentos de grãos desta cultura (Cardwell, 1982), apesar de seus efeitos dependerem de fatores genotípicos (Carlone & Russell, 1987) e ambientais (Bondavalli et al, 1970). Novais et al (1974), Fox et al (1986) e Melgar et al (1991) demonstraram que o parcelamento da adubação nitrogenada proporciona rendimentos de grãos de milho superiores aos obtidos com a aplicação do N de uma só vez, especialmente quando esta aplicação total é feita em determinadas épocas.…”
Section: Introductionunclassified